2021
DOI: 10.1186/s40677-021-00194-y
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction in Palu: the cause of massive mudflows

Abstract: The 7.5 Mw tectonic earthquake that hit Palu City on 28 September 2018 was followed by tsunami and liquefaction, triggered massive mudflows in Balaroa, Petobo, and Jono Oge areas. This study focuses on the generating factors of liquefaction such as the condition of soil lithology, depth of water table, the distance to the focal mechanism, and the thickness of soft sediment. Microtremor data, including the Horizontal Vertical Spectral Ratio (HVSR), geological condition, and borehole data, were examined to condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The earth lining irrigation canal in the Jono Oge area experienced a large deformation and lateral spreading when the earthquake hit on September 28, 2018. Other studies concluded that water flow on the Gumbasa Irrigation Canal also accelerated the emergence of mudflows through the ground fractures [17]. In addition to understanding the geotechnical conditions of the soil around the irrigation canal is needed.…”
Section: Mitigation Plan On the Irrigation Canalmentioning
confidence: 99%
“…The earth lining irrigation canal in the Jono Oge area experienced a large deformation and lateral spreading when the earthquake hit on September 28, 2018. Other studies concluded that water flow on the Gumbasa Irrigation Canal also accelerated the emergence of mudflows through the ground fractures [17]. In addition to understanding the geotechnical conditions of the soil around the irrigation canal is needed.…”
Section: Mitigation Plan On the Irrigation Canalmentioning
confidence: 99%
“…Historically, as of 2019, there are minimally 37 liquefaction disasters already happened in Indonesia [1]. One of the latest and biggest damages of liquefaction, in Indonesia, was the massive mudflows in Balaroa, Petobo, and Jono Oge, Central Sulawesi which happened in early October 2018 [2]. The 7.5 Mw tectonic earthquake that happened on 28 September 2018 was the major triggering factor responsible for the flow slides [3].…”
Section: Introductionmentioning
confidence: 99%
“…Roughly 63 percent of the victims of the 2011 Japan tsunami in Ishinomaki occurred in their houses [1]. In addition, the settlement in the Balaroa, Petobo, and Jono Oge regions had sunk because of the tremendous liquefaction caused by the Palu earthquake disaster [2]. Examples of cascading chains of geological events include: earthquake rupture creating tsunami; intense earthquake shaking prompting large-scale landslide and liquefaction, and mainshock causing a series of destructive aftershocks [3].…”
Section: Introductionmentioning
confidence: 99%